Bargaining in rural households a study of decisions on labor market participation in the Cordillera - Mendoza, Lorelie Crisologo; Berlage, Lodewijk (The Philippine Review of Economics, 2006)
In this paper we derive testable implications of a unitary farm household model and a non-unitary, i.e., bargaining, model. In the unitary household model the impact of spouse-specific resources and nonlabor income on household decisions should not be different from the model where the resources and nonlabor income are common to the household. In a bargaining model we expect to find impact of spouse-specific resources and nonlabor income. Our empirical tests are based on a small survey of households in the Cordillera region of Northern Luzon (Philippines). In this region each spouse retains specific rights on her or his inherited land, although within marriage this land is treated as part of the household farm. Inherited land is a truly exogenous variable, which we use as the indicator of bargaining power. We perform probit regressions in which the spouses' inherited land is a determinant of the probability that a husband or wife participates in the labor market. The statistical results provide some evidence of impact of spouse-specific resources on labor market participation decisions, and thus cast doubt on the unitary farm household model. They are compatible with the bargaining model of household behavior.